ANALISIS TEKS PIDATO PARIWISATA BUDAYA DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA SISWA SMAN 3 DENPASAR (Widyadari, 2024)
Cultural tourism is a form of tourism that focuses on preserving culture and provides positive benefits for students and can be a source of ideas for developing creativity in writing speech texts. However, there are still many students who experience difficulties in analyzing speech texts. The aims of this research are (1) to determine the ability to analyze speech texts with a cultural tourism theme, (2) to find out the difficulties faced when analyzing speech texts with a cultural tourism theme, and (3) to find out the factors that cause when analyzing speech texts themed cultural tourism. The research subjects were class X students at SMA Negeri 3 Denpasar for the 2023/2024 academic year. The methods used to collect data are the test method, questionnaire method, and interview method. The difficulties experienced by students include several aspects, namely 49.1% experienced difficulty in determining the introduction to the speech, 63.2% experienced difficulty in determining the content of the speech, and 54.8% experienced difficulty in determining the conclusion of the speech. The factors causing the difficulties experienced are students' lack of understanding of the structure of the speech, especially at the beginning and core of the speech, students' lack of understanding of the stages of analyzing a text. Thus, the ability to analyze students' cultural tourism-themed speech texts is in the good category.